Bioenergetics of Islet Preparations in a Pilot Clinical Trial of Peri-Transplant Hydroxychloroquine for Autologous Islet Transplantation. (10th November 2021) - McDowell, Ruth E.; Ali, Khawla F.; Lad, Saloni; San Martin, Vicente T.; Bottino, Rita; Walsh, Matthew; Stevens, Tyler; Wilke, William; Kirwan, John P.; Hatipoglu, Betul
The inflammatory response is an obstacle to success in both allogeneic and autologous islet transplantation. In autologous islet transplantation (AIT), however, the recipient is also the donor, permitting pretreatment of donor/recipient for a controlled duration prior to transplantation. We sought to exploit this feature of (AIT) by pretreating donor/recipients with chronic pancreatitis undergoing total pancreatectomy and autologous islet transplantation (TPAIT) to test the hypothesis that peri-transplant treatment with the FDA-approved anti-inflammatory hydroxychloroquine (HCQ) improves graft function. In this randomized placebo-controlled pilot clinical study, patients ( n = 6) were treated with oral HCQ for 30 days prior to and 90 days after TPAIT. In vivo islet function was assessed via Mixed Meal Tolerance Testing before HCQ treatment, 6- and 12-months after surgery. In vitro islet bioenergetics were assessed at the time of transplantation via extracellular flux analysis of islet preparation samples from the clinical trial cohort and six additional patients ( n = 12). Our study shows that HCQ did not alter clinical endpoints, but HCQ-treated patients showed greater spare respiratory capacity (SRC) compared to samples from control patients ( P =0.028). Glycolytic metabolism of islet preparations directly correlated with stimulated C-peptide secretion both before and after TPAIT ( P =0.01, R 2 =0.489 and P =0.03, R 2 =0.674, respectively), and predicted in vivo islet function better than mitochondrial metabolism of islet preps or islet equivalents infused. Overnight culture of islet preparations altered bioenergetic function, significantly decreasing SRC and maximal respiration ( P <0.001). In conclusion, while HCQ did not alter clinical outcomes, it was associated with significantly increased SRC in islet preparations. Bioenergetic analyses of islet preparations suggests that culture should be avoided and that glycolysis may be a more sensitive indicator of in vivo islet function than current metrics, including islet oxygen consumption and islet equivalents infused.